Memprediksi kepuasan hidup karyawan Kristen di Indonesia: Menguji peran religiositas, persepsi dukungan organisasi, dan makna kerja - Seger Handoyo; Jenny Lukito Setiawan; Yusak Novanto (Konsorsium Psikologi Ilmiah Nusantara, 2022)
Life satisfaction plays important role in employees’ work performance and is related to the internal factors of religiosity, perceived organizational support, and meaningful work. This research aims to investigate the influence of religiosity and perceived organizational support on life satisfaction through meaningful work as a mediator for 263 respondents from 118 organizations in Indonesia. This research found that a significant number of participants (71.86%) were satisfied with their life. The findings show that religiosity and perceived organizational support enhance their life satisfaction such that meaningful work is a partial mediator for these relationships. Organization leaders should maintain employees’ life satisfaction through religious activities and provide them with organizational support.